Bibliometric insights in fournier's gangrene: Research landscapes, turning points, and global trends - Jia-Yuan Zhang; Chang-Fang Xiao; Chen Wang; Yi-Bo Yao (Frontiers in Surgery, 2023)
Study DesignBibliometric and visualization analysis.ObjectiveTo analyze the research landscapes and hotspots of Fournier's gangrene, and reveal the dynamic changes and development trend of research hotspots for the purpose of providing ideas and a basis for clinical and basic research in this field.MethodsResearch datasets were acquired from the Web of Science. The publication years were limited from January 1, 1900 to August 5, 2022. The bibliometric tools CiteSpace (v5.8) and VOSviewer (v1.6) were used to analyze the data and generate visualization knowledge maps. Trends in annual publications, distribution, H-index status, coauthorships status and research hotspots were analyzed.ResultsAccording to the search strategy, we identified and enrolled 688 publications regarding to Fournier's gangrene. The number of published papers showed an overall upwards trend. The USA was the largest contributor, ranking first in total publications, citations and the H-index. The top 10 most productive institutions were all from the USA. De Simone B and Sartelli M were the most productive authors. There was close cooperation among countries, but the cooperation among institutions and authors had little contact and poor interactivity. The research hotspots included the pathogenesis factors and treatment. All the identified keywords were divided into 14 clusters, and the label of the latest cluster was “empagliflozin”. Prognosis and risk factors, emerging treatment methods, and pathogenesis were at the forefront of the Fournier's gangrene field and were predicted to be the next hot topics.ConclusionThe research of Fournier's gangrene has made some achievements, but the overall research level is still in the primary stage. The academic cooperation between different institutions and authors needs to be strengthened. At the early stage, the mainstream of research was the infected tissue and site, pathogenesis, and diagnosis of disease, while research on newly discovered sodium-glucose cotransporter 2 inhibitor, adjuvant therapy and prognostic factors may be the main directions in the future.